PDPIPS technique in Malay language speech - Mohd Kiram, Norazlina (Human Resource Management Academic Research Society, 2023)
Speech is the art of public speaking, thereby the sharing of information and messages between orators and the audiences. Speech text writing is paramount to ensure the message could be delivered effectively to the audience. However, not many orators have the ability to produce a quality speech text. Some speeches are chaotic and the messages are difficult to understand. PDPIPS technique is a new approach to helps orators to improve public speaking in Malay language. Hence, this article is to introduce the PDPIPS (Introduction, Definition, Position, Content, Conclusion and Suggestion) Technique in developing clear ideas, structured and subsequently able to entice audience’s attention. A qualitative research design and content analysis methods are used in this research.The PDPIPS technique is an enhancement from the conceptual framework developed by Arndt Graf (2011), which outlines three components, namely Introduction, Content and Conclusion. The data of the study is taken from the speech text of the participant in Pertandingan Gegar Pidato Piala Ketua Pengarah Perkhidmatan Awam 2019. The speech text was prepared by the author and won the runnerup at the national level. The research finding shows that PDPIPS Technique should be adopted in order to produce a good speech text, therefore organise ideas systematically, clearly and effectively. By using PDPIPS technique, an orator’s image could be improved as a competent and proficient in Malay language, in addition to language politeness. In general, the PDPIPS Technique can increased orators self-confidence and convincing the ideas through oratory skills.